(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Skin diseases constitute 6-24% of all pediatric consultations worldwide. The most frequently encountered dermatoses in children - atopic dermatitis, seborrheic dermatitis, impetigo, scabies, tinea corporis, psoriasis, and molluscum contagiosum - share overlapping morphological features that complicate clinical differentiation. Accurate diagnosis requires systematic integration of age at onset, lesion distribution, associated symptoms, family history, and targeted laboratory investigations including microscopy, bacterial culture, and dermoscopy. This review presents quantitative epidemiological data and evidence-based differential diagnostic criteria for the most common pediatric dermatoses.